Prostate cancer : basic mechanisms and therapeutic approaches - Chang, Chawnshang, 1955- (World Scientific, 2005)
Prostate cancer is the second leading cause of death in men and its progression is highly dependent on androgens and androgen receptors. However, even with treatment, eventually most prostate cancers progress. Studies of the mechanisms behind this progression leads to advances in treatments for androgen-related diseases. Our book discusses recent prostate cancer research, which includes the following topics: immunotherapy and chemotherapy; radiation, gene, hormonal, and androgen ablation therapies; basic mechanisms behind prostate cancer growth; how mechanisms can be used to treat prostate can.